2013
DOI: 10.1002/ett.2731
|View full text |Cite
|
Sign up to set email alerts
|

Active spectrum sensing for cognitive radio networks

Abstract: An energy detection-based active spectrum sensing scheme is proposed to carry out spectrum sensing and secondary transmissions simultaneously. It successfully avoids the widely used quiet periods, which have at least two shortcomings. First, periodical interruptions of secondary transmissions degrade the quality of service of secondary networks (e.g. decreasing the system capacity and increasing end-to-end packet delay). Second, frequent tight synchronisation is necessary but very difficult to implement in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Evaluations showed a fairly good performance of the proposed technique with low degradation in terms of throughput. Similarly, reducing the frequency of sensing operations was the main goal of Zhao and Sasaki as well. However, they were trying to eliminate the need for quiet period when energy detection is used.…”
Section: Related Workmentioning
confidence: 99%
“…Evaluations showed a fairly good performance of the proposed technique with low degradation in terms of throughput. Similarly, reducing the frequency of sensing operations was the main goal of Zhao and Sasaki as well. However, they were trying to eliminate the need for quiet period when energy detection is used.…”
Section: Related Workmentioning
confidence: 99%
“…This scenario is considered in , where an interference‐mitigation scheme close to macrocell/femtocell real‐life scenario is experimentally evaluated. Another recent work that takes into account interference in the CR context is , where, with the assistance of geolocation information, a sensing scheme that decomposes the received power into the primary signal power, secondary signal power (treated here as interference) and the device noise power is proposed. In this way, after decomposing the total power, the interference power can be canceled prior to PU detection.…”
Section: Introductionmentioning
confidence: 99%
“…Kalamkar et al [6] have studied the detection performance of energy detector under different distribution of noise uncertainty and their effects on generalized energy detector. An active spectrum sensing scheme based on energy detector was proposed by B.Zhao et al [7]. It was concluded that the performance of the suggested sensing scheme was degraded in Rayleigh fading condition but their performance can be enriched by spending prolonged observation time which is comparable to AWGN channel.…”
Section: Introductionmentioning
confidence: 99%